Clinical outcome of early versus late interventions in pediatric intestinal obstruction: A retrospective study - Arzoo D (Bioinformation, 2026)
Pediatric intestinal obstruction is a surgical emergency in which delayed treatment increases morbidity and mortality. Therefore, it is of interest to compare the outcome of early and delayed intervention in 126 children treated between 2019 and 2024. Early intervention within 24 hours significantly reduced bowel gangrene, bowel resection, surgical site infection and mortality. Children receiving early treatment also had a significantly shorter hospital stay than those managed after 24 hours. Thus, timely resuscitation and early operative or non-operative management improve clinical outcomes in pediatric intestinal obstruction.